Theoretical bases of formation EQUITY - Baimukhanova, S.B. (Journal of Economic Research & Business Administration, 2016)
The main objectives of this study is to validate the importance of knowledge of the theoretical foundations of the formation of equity capi-tal, which contribute to the correct and complete perception and, as a consequence, their use in practice. Therefore, this article deals with the theoretical basis for the formation of own capital, studying the works of a number of Letter of zaubezhnyh and authors on the problem, the author defends his point of view and justify their value and contrast.The originality of the research is to obtain scientific results, which formed the conceptual apparatus of research shows the essence, signifi-cance and role of equity capital as the main source of solvency and finan-cial stability of the organization.